IMPLEMENTASI PENJAMINAN HAK ANAK DAN ISTRI PERSPEKTIF HUKUM POSITIF DI INDONESIA - Patrajaya, Rafik (SANGAJI: Jurnal Pemikiran Syariah dan Hukum, 2017)
One of the interest point to study is how the positive low guarantee the right of family’s low. This paper talk about some problems about the implementation of guarantee right primarly the low of family, Right should see the equal and same in family and social life as the important problem must be solved. As principle of marriages in The constitution No.1, 1974 chapter 31 clearly said that position between Husband and wife is same, it can be running in family and social life. Husband as the a leader of family meanwhile wife as a housewife, they has the right to be the subject in low. The other bill range clearly about caring The Kid’s Right, it explains that the Kid must be cared and teach until they married or the live independent although their parents divorced. The Kids who is not 18 years old or never married, they are still under parents caring as long as the power is canceled yet. In this term, Parents have the right to vice their kids in all of low’s activities out and in the justice. Event though, parents are canceled their power however they have to give the budget’s caring to their kids